Jumlah Penerbangan Terhadap Jumlah Penumpang pada Antrian Check In Counter - Djoko Priambodo; Putri Silvia; Endang Wahyuni (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The purpose of this study is to determine the amount of flights and passengers at the Terminal 1A Check-in Counter at Soekarno Hatta Airport. The study used simple linear regression analysis techniques, correlations, determinant coefficient and hypothesis testing. The results of this study show that the regression coefficient analysis, -15859.152 + 164.628X constant of -15859.152 states that if there is no increase in the value of the variable amount of flights (X) then the amount of passengers at Check-in Counter Terminal 1A at Soekarno Hatta Airport will decrease -15859.152. It means that if there is no increase in the amount of flights, the amount of passengers at the Check-in Counter will decrease, whereas if there is an increase in the amount of flights, the amount of passengers at the Check-in Counter will increase. Correlation coefficient, states the price r = 0.943 means that the value of the amount of flights to the amount of passengers at the Check-in Counter is very strong. KP determinant coefficient = 88.9% means that there is an influence from variable amount of flights to the amount of passengers in the Check-in Counter at Terminal 1A at Soekarno Hatta Airport, because tcount> ttable (13,304> 2,074) then Ho is rejected and H1 is accepted, meaning partially there is a significant influence between the amount of flights on the amount of passengers in the Check-in Counter at Terminal 1A at Soekarno Hatta Airport.